Achieving universal access to obstetric ultrasound in resource constrained settings: A narrative review. Issue 2 (May 2021) - Luntsi, G.; Ugwu, A.C.; Nkubli, F.B.; Emmanuel, R.; Ochie, K.; Nwobi, C.I.
Abstract: Objectives: The potential benefits and challenges of achieving universal access to obstetric ultrasound services in resource constrained settings were reviewed, with a view to making some recommendations to address the huge burden of avoidable maternal and child morbidity and mortality. Key findings: In most resource-poor settings of the world, antenatal ultrasound is available only to a privileged few in urban centres, while the majority of the population living in rural areas have little or no access to diagnostic imaging services. There is also the extreme shortage of sonographers and doctors with specialist training in sonography. A comprehensive regulation must be put in place to achieve maximum benefits and to ensure quality assurance; appropriate use and application of ethics and training must be comprehensive. Conclusion: Ultrasound service provision, in resource-scarce settings, has the potential to improve access and quality of health care services in areas like the point of care ultrasound service provision and in the fields of obstetrics and gynaecology. A comprehensive regulation must be put in place to achieve maximum benefits and to ensure quality assurance. Implications for practice: Making ultrasound technology available and affordable in resource scare settings has the potential to improve access to diagnostic imaging services and reduce avoidable maternal and child death in resource constrained settings.